Clinicopathological features of cutaneous reactions after mRNA‐based COVID‐19 vaccines. (16th September 2021) - Tihy, M.; Menzinger, S.; André, R.; Laffitte, E.; Toutous‐Trellu, L.; Kaya, G.
Abstract: Background: Cutaneous reactions, mostly on injection site after mRNA‐based COVID‐19 vaccines, have been reported but not with detailed histopathological characterization. Objectives: Characterization and classification of these reactions in a clinical and pathological point of view. Methods: Monocentric case series of 11 patients with cutaneous manifestations, clinically and histologically characterized after COVID‐19 vaccination. Results: From January to June 2021, we recorded 11 cutaneous reactions to mRNA COVID‐19 vaccines from BNT162b2 ( n  = 8) and mRNA‐1273 ( n  = 3). Generalized reactions showing erythematous rash or purpura were the most common clinical presentation, and drug‐reaction‐like pattern was the most common histological finding. Conclusions: A proper clinicopathological classification will be helpful in the early diagnosis and management of the cutaneous reactions to mRNA COVID‐19 vaccines.